UTILIZATION OF TECHNOLOGY AS A CREATIVE LEARNING MEDIA AND INNOVATIVE IN THE MILLENIAL GENERATION IN THE NEW NOERMAL ERA: A LITERATURE STUDY - Kholillah Widia; Laila Dyah Pitaloka (International Conference on Social and Islamic Studies, 2021)
This research is a literature review. This study aims to examine the use of technology as acreative and innovative learning medium for the millennial generation in the new normal era.The author uses a qualitative research methodology and the data used comes from relevantliterature studies such as books, journals, theses and websites that can be accounted for for thecorrectness of the data. The object of this research is the millennial generation. The results of thisstudy indicate that the use of technology as a creative and innovative learning medium for themillennial generation in the new normal era is very important in the teaching and learningprocess in order to make it easier for educators to communicate and interact with students insideand outside the classroom. The need for technology in education is not new, the use oftechnology in this new normal era aims to develop capable and creative students.